Unraveling the LRC Evolution in Mammals: IGSF1 and A1BG Provide the Keys - Guselnikov, Sergey V (Genome Biol Evol, 2019)
Receptors of the leukocyte receptor cluster (LRC) play a range of important functions in the human immune system. However, the evolution of the LRC remains poorly understood, even in m\ammals not to mention nonmammalian vertebrates. We conducted a comprehensive bioinformatics analysis of the LRC-related genes in the publicly available genomes of six species that represent eutherian, marsupial, and monotreme lineages of mammals. As a result, the LRCs of African elephant and armadillo were characterized, two new genes, IGSF1 and A1BG, were attributed to the LRC of eutherian mammals, the LRC gene content was substantially extended in the short-tailed opossum and Tasmanian devil and, finally, four LRC genes were identified in the platypus genome. These findings have for the first time provided a solid basis for inference of the LRC phylogeny across mammals. Our analysis suggests that the mammalian LRC family likely derived from two ancestral genes, which evolved in a lineage-specific manner by expansion/contraction, extensive exon shuffling, and sequence divergence. The striking structural and functional diversity of eutherian LRC molecules appears largely lineage specific. The only family member retained in all the three mammalian lineages is a collagen-binding receptor OSCAR. Strong sequence conservation of a transmembrane domain known to associate with FcRγ suggests an adaptive role of this domain subtype in the LRC evolution.